Nucleotide sequence of the primary origin of bacteriophage T7 DNA replication: relationship to adjacent genes and regulatory elements. - Saito, H (1980)
The 682-base-pair nucleotide sequence between positions 14.45 and 16.15 on the bacteriophage T7 DNA molecule has been determined. We can identify not only the sequence of the primary origin of DNA replication but also the termination of gene 1, all of genes 1.1 and 1.2, the start of gene 1.3, and a number of regulatory sequences. The endpoints of four deletion mutations that extend into this region have been determined. These mutations are inferred to have arisen by recombination between short homologous sequences, three of which ar T7 RNA polymerase promoters. The base changes of four point mutations in gene 1.2 have been identified. The sequence essential for initiation at the primary origin is located between the left endpoints of the two deletions D2 and D303. Sequence analysis of these mutants assigns the primary origin to a 129-base-pair segment between positions 14.73 and 15.05. This intergenic segment is A+T-rich (75%) and contains a single T7 gene 4 protein recognition site; it is preceded by two tandem T7 RNA polymerase promoters. A model for initiation of T7 DNA replication is presented.